Alignment between teacher performance standards and preschool curriculum - Edna Luna Serrano; Luis Horacio Pedroza Zuñiga; Perla Lizeth Cordova Valenzuela (Arizona State University, 2019)
In a school system oriented to the fulfillment of educational objectives and the improvement of teaching performance, the congruence between the normative documents and the evaluation of teaching is fundamental. From this perspective, the objective of this study was to analyze the alignment between the implicit teaching competencies of the Preschool Studies Program and the performance teaching standards, as well as assessing the agreement between two versions of the standards issued by the Mexican Ministry of Education. To address those objectives the methodology included two descriptive studies, which apply content analysis techniques as well as work with subject matters judges, the curriculum alignment technique and Bloom's revised taxonomy. In general, the standards are aligned with the Program, except in the areas of formative evaluation and the use of play as a didactic strategy; in the last version of the standards the demands of the cognitive process were lower in the taxonomy. The conclusion suggests an integrated evaluation system that recognizes all specific aspects of preschool teaching practice.